2023
DOI: 10.3390/antibiotics12030486
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Efflux Pump Mutations in Pseudomonas aeruginosa from Clinical Samples

Abstract: Efflux pumps are a specialized tool of antibiotic resistance used by Pseudomonas aeruginosa to expel antibiotics. The current study was therefore conducted to examine the expression of MexAB-OprM and MexCD-OprJ efflux pump genes. In this study, 200 samples were collected from Khyber Teaching Hospital (KTH) and Hayatabad Medical Complex (HMC) in Peshawar, Pakistan. All the isolates were biochemically identified by an Analytical Profile Index kit and at the molecular level by Polymerase Chain Reaction (PCR) util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Our data has shown that MexB seems to contribute the most within the MexAB-OprM efflux pump system towards the antibiotic-resistance phenotype. Also, studies on multidrug resistant P. aeruginosa strains isolated from hospitals by Bialvaei et al reported that the overexpression of mexB and mexY was significantly more prevalent in the studied strains, with a significant correlation with antibiotic resistance [7,33]. Altogether, the efflux pumps play important roles in increasing the resistance towards different antibiotics, but the role of other agents and mechanisms in the evolution of resistance should not be ignored.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our data has shown that MexB seems to contribute the most within the MexAB-OprM efflux pump system towards the antibiotic-resistance phenotype. Also, studies on multidrug resistant P. aeruginosa strains isolated from hospitals by Bialvaei et al reported that the overexpression of mexB and mexY was significantly more prevalent in the studied strains, with a significant correlation with antibiotic resistance [7,33]. Altogether, the efflux pumps play important roles in increasing the resistance towards different antibiotics, but the role of other agents and mechanisms in the evolution of resistance should not be ignored.…”
Section: Discussionmentioning
confidence: 91%
“…The presence of these efflux pumps poses a significant challenge in managing multidrugresistant P. aeruginosa infections, emphasizing the need for a comprehensive understanding of their underlying mechanisms. Moreover, exploring the development of efflux pump inhibitors holds promise as a potential adjunctive therapy to address the complexities associated with P. aeruginosa infections, particularly those involving multidrug-resistant strains [5][6][7].…”
Section: Introductionmentioning
confidence: 99%